Pengaruh Kualitas Layanan Bus Transjakarta Terhadap Kepuasan Konsumen - Jeremiah Jeremiah; Jessica Dasaria; Mahendra Kresna Putra; Michael Seninha; Vivi Vyolina (Indonesian Business Review, 2019)
Service quality is one of the most important factor that influences customer satisfaction level, likewise customer satisfaction will greatly influence repurchase intention level. This statement is hold true in case of public transportation service, including Transjakarta. This research measures service quality perceived by Transjakarta commuters and its correlation with customer satisfaction level and its corresponding correlation with repurchase intention level. The outcomes show that 3 factors: comfort, reliability , and employee performance significantly correlated with customer satisfaction level that also significantly correlated with repurchase intention level. This three factors should become the focus of improvement in order to maximize Transjakarta 's role.